2005
DOI: 10.1038/nature03527
|View full text |Cite
|
Sign up to set email alerts
|

Vascular respiratory uncoupling increases blood pressure and atherosclerosis

Abstract: The observations that atherosclerosis often occurs in non-smokers without elevated levels of low-density lipoprotein cholesterol, and that most atherosclerosis loci so far identified in mice do not affect systemic risk factors associated with atherosclerosis, suggest that as-yet-unidentified mechanisms must contribute to vascular disease. Arterial walls undergo regional disturbances of metabolism that include the uncoupling of respiration and oxidative phosphorylation, a process that occurs to some extent in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
115
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(120 citation statements)
references
References 24 publications
4
115
0
1
Order By: Relevance
“…A blunted or absent increase in shear stress and NO-induced vasodilatation in peripheral arteries may result in increased vascular resistance and inadequate blood supply, further worsening the energetic imbalance in skeletal muscle because of ineffective ATP generation. Recent data from experimental models indicate that mitochondrial dysfunction is associated with cardiovascular alterations including increased blood pressure, atherosclerosis, and premature aging (32,33). Moreover, mtDNA mutations have been associated with increased blood pressure also in humans (34 -37).…”
Section: Discussionmentioning
confidence: 99%
“…A blunted or absent increase in shear stress and NO-induced vasodilatation in peripheral arteries may result in increased vascular resistance and inadequate blood supply, further worsening the energetic imbalance in skeletal muscle because of ineffective ATP generation. Recent data from experimental models indicate that mitochondrial dysfunction is associated with cardiovascular alterations including increased blood pressure, atherosclerosis, and premature aging (32,33). Moreover, mtDNA mutations have been associated with increased blood pressure also in humans (34 -37).…”
Section: Discussionmentioning
confidence: 99%
“…1 We and other investigators had already reported that experimental atherosclerosis in apoE-deficient mice was markedly suppressed by the Fcγ portion of immunoglobulin administration, possibly by an antiinflammatory action via the inhibitory Fcγ receptor IIB. [19][20][21] There is also increasing evidence to support the critical role of both free radicals and oxidative stress in the development of atherosclerosis [22][23][24][25] and in heart failure. 26,27 We had already demonstrated that MCI-186, a free radical scavenger, and olmesartan, an angiotensin type 1 receptor antagonist, suppress the severity of experimental atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Several enzymes have been implicated as possible sources of elevated ROS in hypertension, including NADPH oxidase, 14,15 xanthine oxidase, 16 NO synthase (NOS), 17 cyclooxygenase, 18 and mitochondrial electron transport leakage. 19 It has been suggested that reductions of enzymes that scavenge ROS, such as superoxide dismutases (SOD), 20 catalase, and glutathione peroxidase (GPx), may also play a role. In the present study, we explored which of these many pathways most importantly determines the susceptibility of the SS rat to salt-induced hypertension.…”
mentioning
confidence: 99%